Pengaruh Menopause Terhadap Kecenderungan Depresi Ibu-ibu PKK Desa Sidomulyo Kecamatan Batu Kota Batu - Yumei Astutik; Syaiful Hadi (Ilmu Psikologi Universitas Yudharta Pasuruan)
Menopause constitutes a life deep step all woman and necessarily this condition gets to be accepted and is behaved wisely, since if woman enters particular age which is final adulthood period, period menopause must upcoming. But is not all woman get to behave it with able, since a lot of within women while begins to enter this period one be pointed out with physical phenomenas, psychological and social, perceive fidget, alarm even depression which make women experiences behaviour change. This research is done on 105 membered mothers of PKK Sidomulyo's Villages already enter menopause's periods and its result points out that menopause kicks in 32,182% for its heavyhearted happening and its residuary because of unanalyzed other factors.